Corporate Reputation: Being Good and Looking Good. Issue 6 (July 2019) - Chun, Rosa; Argandoña, Antonio; Choirat, Christine; Siegel, Donald S.
This article introduces the special issue on "Corporate Reputation: Being Good and Looking Good." Three of the five included articles help to reinforce a conclusion that "being good" and "looking good" are not dichotomous, mutually exclusive conditions. Rather, the two dimensions are linked in some kind of causal relationship for which continuing conceptual and empirical research is desirable. A fourth article concerns the reputational effects of the stock-option backdating scandal. The fifth article offers a critique of conventional approaches to defining and measuring reputation.